Descentralização territorial da educação profissional e tecnológica no Paraná: determinante de desenvolvimento local? - Beloni, Belmiro Marcos (2014)
This paper aims to conduct a geo-economic and political study of the relationship between economic development and internalization of vocational and technological education in institutionalized Federal Technological University of Paraná - UTFPR. The guiding question is: Why vocational and technological education? Why and how the internalization of Federal Center of Technological Education - CEFET-PR occurred in these cities? A technological university in its centenary route developed systematically during much of its history, a subject pragmatic and utilitarian education demands of productive transformation, responsible for technical education. The institutional differentiation, first as multicampus institution and subsequently as a specialized university advancement provided with the maintenance of the previous bases. The bottleneck of educational policies towards spatialization of federal universities via Plan of Reorganization and Expansion of Federal Universities - REUNI, makes the previous UTFPR in the process, justifying the need analysis of the different effects in the implementation of the decentralized units in the inner cities of Paraná, especially as vector of local/regional development , diversification economic and employability .